Exploring global dynamic managerial capabilities and firm innovativeness in fintech-oriented firms: evidence from Jordan’s Industry 4.0 context - Salih, Rediyar; Bndyan, Qasim; Mousa, Kawar Mohammed; Ali, Khairi Ali Auso; Ahmed, Dildar Haydar; Baykan, Hüseyin (Frontiers in Human Dynamics, 2026)
In today’s fast-evolving digital economy, managers play a critical role in driving innovation, particularly in the dynamic and high-risk fintech sector. This study investigates how global dynamic managerial capabilities (GDMC), including social capital, human capital, and cognitive skills, affect the innovative performance of fintech firms. Based on 205 valid responses from Jordanian manufacturing companies operating under Industry 4.0 conditions, regression analysis was applied to examine these relationships. The individual components of GDMC did not show a significant impact on innovation when assessed separately. However, when considered together, they had a strong, positive influence on firm innovativeness. These results emphasize the value of an integrated managerial capability profile, particularly in digital business environments. Extending the GDMC framework to the fintech context, this study adds evidence that combined managerial strengths can support innovation and help firms build a competitive edge in tech-driven industries.